Nonlinear Analysis on Torsional Strengthening Of Rc Beams Using Cfrp Laminates (Journal of Engineering, 2013)
This research is devoted to investigate the behavior and performance of reinforced concrete beams strengthened with externally bonded Carbon Fiber Reinforced Polymer (CFRP) laminates under the effect of torsion. In this study a theoretical analysis has been conducted using finite element code ANSYS. Six previously tested beams are used to investigate reinforced concrete beams behaviorunder torsion, two of them are solid and the rest are box-section beams. Also, two beams are without CFRP reinforcement, which are used as control beams for the strengthened one, and the other four beams are strengthened with CFRP laminates with different number of layers and spacing. Numerical investigation is conducted on these beams, and comparisons between the available experimental results for these beams and numerical results from the current study are made. Conclusions from these comparisons are presented and discussed. An increase of about 15.6% in the ultimate torque for the solid beam and of about 9.8% in the ultimate torque for the box-section beam is observed after using the CFRP strips. A parametric study is carried out to study the torsional behavior of RC beams having different number of CFRP layers and concrete compressive strength; also U-wrap for the CFRP configuration is investigated.